a-tocopherol content and susceptibility to lipid peroxidation in muscle from Iberian pigs fed in two different recebo systems - Tejeda J.F.; González E. (5. International Symposium on the Mediterranean Pig, 2007)
The a-tocopherol content and susceptibility to lipid peroxidation in Gluteo biceps muscle from Iberian x Duroc (50%) pigs were analysed. The a-tocopherol content was higher (p<0.01) in muscle from recebo 2 pigs, which consumed higher quantities of vitamin E enriched concentrate feed (220 mg/kg) during the fattening period, than in recebo 1 pigs. Susceptibility of the muscle to lipid oxidation was significantly (p<0.01) influenced by the feeding system, animals reared in recebo 1 system showing higher levels of MDA after 50 and 100 min of incubation than recebo 2 pigs. These results indicate that a-tocopherol content in the muscle depends on the levels of this natural antioxidant provided by dietary means.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)